2021
DOI: 10.1109/tbme.2020.3006934
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Impedance-Based Estimation of Cochlear Implant Electrode Array Insertion Depth

Abstract: Cochlear implant impedances are influenced by the intracochlear position of the electrodes. Herein, we present an intuitive approach to calculate tissue resistances from transimpedance recordings, ultimately enabling to estimate the insertion depth of cochlear implant electrodes. Methods: Electrode positions were measured in computed-tomography images of 20 subjects implanted with the same lateral wall cochlear implant model. The tissue resistances were estimated from intraoperative telemetry data using bivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 39 publications
1
45
0
Order By: Relevance
“…To enable a large number of insertions, we produced electrode array dummies that match the mechanical characteristics of a long free-fitting clinical array (Flex 28 , MED-EL GmbH, Innsbruck, Austria) [39]. We chose this particular type of array because it is the most commonly used in our clinic and enables us to monitor deep insertions [40], [41]. The dummies have the same dimensions as the clinical arrays, with a circular cross-section (diameter 0.8 mm) at the base morphing into an elliptical shape (0.5 mm × 0.4 mm) at the tip.…”
Section: A Experimental Setupmentioning
confidence: 99%
“…To enable a large number of insertions, we produced electrode array dummies that match the mechanical characteristics of a long free-fitting clinical array (Flex 28 , MED-EL GmbH, Innsbruck, Austria) [39]. We chose this particular type of array because it is the most commonly used in our clinic and enables us to monitor deep insertions [40], [41]. The dummies have the same dimensions as the clinical arrays, with a circular cross-section (diameter 0.8 mm) at the base morphing into an elliptical shape (0.5 mm × 0.4 mm) at the tip.…”
Section: A Experimental Setupmentioning
confidence: 99%
“…The relationship between insertion depth and monopolar impedances (Fig. 1, top left) was identified by Giardina et al [14] and Aebischer et al [15]; Aebischer et al showed a relationship strong enough to enable accurate prediction of insertion depth based on monopolar impedance measurements alone.…”
Section: Introductionmentioning
confidence: 88%
“…This is because monopolar access resistance measures the resistive path between an intracochlear electrode and the ground. As the conductivity of the intracochlear fluid is nine times higher than the conductivity of bone [29], while the transversal resistances of the basal-most electrodes are on average 16 times smaller than the other transversal resistances [15], a large proportion of the current will flow through the intracochlear fluid and exit basally. This causes the overall monopolar impedance to be higher for deeper insertions into the cochlea.…”
Section: B Insertion Depth and Impedancementioning
confidence: 97%
“…Electrical impedance is also used for detection of EA insertion failure and translocation [30][31][32]. Most recently, electrode impedance recordings were used for insertion depth estimation [33].…”
Section: Introductionmentioning
confidence: 99%